The Expansion of Sharia Financial Inclusion Through Optimization of Laku Pandai in MSMEs Partners PT. Bank Syariah Indonesia, Tbk - Syah Amelia Manggala Putri; Aqidah Asri Suwarsi; Gina Okta Sari; Maddani Akhsa Nulyani; Rofiul Wahyudi; Eka Jati Rahayu Firmansyah (AKM, 2024)
MSMEs make an optimal contribution to the Indonesian economy. However, currently one of the problems of MSMEs is that they do not have access to products and services to Sharia finance. The majority of MSMEs are also still focused on the main business and have not generated much fee-based income to support their results. The community service team proposed a solution to the problem by implementing Laku Pandai to solve the problem. The output target to be achieved is journal publication, being able to implement Laku Pandai as access to Islamic financial services, and getting fee-based income from its operations. Activities begin with initial surveys, planning activities with partners, implementing activities as well as evaluation and follow-up plans. Activities will be carried out with the active role of partners until partners can apply output targets independently.